Dynamic shieldings for cultural heritage buildings under seismic action. Issue 89 (October 2016) - Carpinteri, Andrea; Fortese, Giovanni; Ronchei, Camilla; Scorza, Daniela; Tasora, Alessandro; Vantadori, Sabrina
Abstract: The goal of the present paper is to numerically investigate the effects produced by a vertical barrier located inside the ground, when the soil is subjected to seismic waves coming from a seismic source with a planar wave front. Firstly, the acceleration field on the ground surface is computed by varying both geometrical and mechanical properties of the barrier in order to determine, through a parametric study, the optimal barrier configuration to minimize the maximum magnitude of surface acceleration inside the shielded zone. Then, the above configuration is employed in the framework of a seismic analysis: a portion of a colonnade in Pompeii (Naples, Italy) is examined, with such a colonnade assumed to be located inside the shielded zone. A comparison of the seismic behaviour of such a heritage building is provided for the two cases of ground with or without the above vertical barrier. Highlights: Seismic waves coming from a seismic source with a planar wave front. Numerical investigation of beneficial effects by a vertical barrier inside the ground. Both geometrical and mechanical properties of the barrier are made to vary. The seismic behaviour of a colonnade in Pompeii (Naples, Italy) is examined.